Redundancy, Diversity, and Interdependent Document Relevance, a summary of the SIGIR 2009 workshop - Radlinski, Filip; Bennett, Paul; Carterette, Ben (SIGIR Forum, 2009)
The goal of the Redundancy, Diversity, and Interdependent Document Relevance workshop was to explore how ranking, performance assessment and learning to rank can move beyond the assumption that the relevance of a document is independent of other documents. In particular, the workshop focussed on three themes: the e ect of redundancy on information retrieval utility (for example, minimizing the wasted e ort of users who must skip redundant information), the role of diversity (for example, for mitigating the risk of misinterpreting ambiguous queries), and algorithms for set-level optimization (where the quality of a set of retrieved documents is not simply the sum of its parts).